Transformasi Rumah Gadang Kaum Melayu Menjadi Homestay dalam Pengembangan Pariwisata Budaya di Nagari Jawi-jawi Guguk Tahun 2017-2025 - Viona Kurnia Safitri; Najmi Najmi (Jurnal Kronologi, 2026)
The Rumah Gadang is a cultural heritage of the Minangkabau people, serving not only as a residence but also as a hub for customary practices, social life, and clan identity. This study aims to analyze the transformation process of the Rumah Gadang belonging to the Melayu clan in Nagari Jawi-Jawi Guguk, Solok Regency, into a culture-based homestay between 2017 and 2025, and to examine its management patterns in supporting cultural tourism development. The study employs the historical method, comprising the stages of heuristics, source criticism, interpretation, and historiography. Data were gathered through interviews with customary leaders, nagari government officials, and homestay managers, and supplemented by documentation and homestay guestbook archives from 2018 to 2025. The findings indicate that the repurposing of the Melayu clan's Rumah Gadang was carried out through a deliberative process involving niniak mamak (traditional leaders), Bundo Kanduang (female leaders), Pokdarwis (tourism awareness groups), the nagari government, and clan members, all while preserving the building's authentic form and traditional architectural values. This transformation was initiated after Nagari Jawi-Jawi Guguk was designated a Cultural Village in 2017, with the Rumah Gadang subsequently utilized as a homestay starting in 2018. The homestay has boosted local economic activity and served as a vehicle for preserving Minangkabau customs and culture through various tourist-engaging cultural activities. However, management still faces challenges, such as limited funding, inadequate supporting facilities, and a decline in visitor numbers during the COVID-19 pandemic. The study demonstrates that utilizing the Rumah Gadang as a homestay represents an adaptive approach to cultural heritage preservation that supports cultural tourism development while strengthening local community empowerment.